2021
DOI: 10.1177/21501327211029800
|View full text |Cite
|
Sign up to set email alerts
|

Polio Supplementary Immunization Activities During COVID-19 Pandemic: Experience from Penampang District, Sabah, Malaysia

Abstract: Background: Polio Supplementary Immunization Activities (SIAs) were carried out in the State of Sabah in response to the Vaccine Derived Poliovirus outbreak declared in December 2019. Prior to this, Malaysia had been polio-free over the past 27 years. This paper reported on the successful implementation of SIAs in the district of Penampang, Sabah, adapting (vaccine administration) to the COVID-19 pandemic. Methods: A series of meticulous planning, healthcare staff training, advocacy, and community engagement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…These community intervention activities increased social and religious belief in the polio eradication mission by establishing a strong, positive relationship between community members and healthcare workers according to Choudhary et al [ 24 ]. While another study done in Sabah, Malaysia, suggested that active participation of local influencers, such religious person, local leader, and retired government servants not only improved the social belief on the SIA activities but contributed to the success of the SIA program [ 26 ]. Although the detailed functions of community mobilizer in each article were not clearly mentioned, the following are some important targets to be achieved suggested by the GPEI, for example, shifting from a campaign-focused approach to instead making investments in sustained trust and relationship building with communities, reviewing accomplishments using the Minimum Quality Standards and Indicators for Community Engagement seeking opportunities for improving social mobilization activities in outbreak settings and including community engagement indicators in campaign preparedness dashboards to ensure social mobilization activities are tracked against meaningful indicators [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…These community intervention activities increased social and religious belief in the polio eradication mission by establishing a strong, positive relationship between community members and healthcare workers according to Choudhary et al [ 24 ]. While another study done in Sabah, Malaysia, suggested that active participation of local influencers, such religious person, local leader, and retired government servants not only improved the social belief on the SIA activities but contributed to the success of the SIA program [ 26 ]. Although the detailed functions of community mobilizer in each article were not clearly mentioned, the following are some important targets to be achieved suggested by the GPEI, for example, shifting from a campaign-focused approach to instead making investments in sustained trust and relationship building with communities, reviewing accomplishments using the Minimum Quality Standards and Indicators for Community Engagement seeking opportunities for improving social mobilization activities in outbreak settings and including community engagement indicators in campaign preparedness dashboards to ensure social mobilization activities are tracked against meaningful indicators [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malaysia recognised the significance of vaccinations in safeguarding long-term public health and established the National Immunisation Programme in 1950, which is a free programme provided for all Malaysian children in government facilities [ 2 ]. The success of the vaccination programme was demonstrated by the decline in the incidence of poliomyelitis since the introduction of the oral polio vaccine in 1972, with no instances documented since 1986 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MyVac initiative is a nationwide volunteer mobilisation programme that engages individuals who are willing to aid the country's COVID-19 immunisation programme by reaching out to normally inaccessible groups of people [3]. Community volunteering also significantly helped supplementary immunisation activities (SIAs) for the polio disease in Sabah [4]. Some of the benefits of volunteering include community empowerment; increased resilience and social connectedness [5]; fostering a sense of communal trust, belonging [6], and support; and improving mental health [7].…”
Section: Introductionmentioning
confidence: 99%